A case study of adult autonomy in English-immersed conversations. Issue 6 (2nd November 2022) - Jin, Xiaoling
ABSTRACT: This paper reports a case study focusing on naturalistic communication between a Chinese beginning non-native speaker of English (NNS) and an English native speaker (NS). The participants engage informally in a form of tandem learning, with each in turn taking the dominant role in the conversation through teaching the other vocabulary items in their L1 (English and Chinese). The study sheds light on some of the conversational and linguistic features of the autonomous Chinese beginner's construction of English conversation. From the conversational patterns identified, we conclude that: (1) NS-beginner NNS conversation works best when it follows a tight turn-by-turn structure; (2) the beginner's initiation of insertion sequences and overlapping can expand conversation; and (3) both beginner NNS and NS need to make great efforts to complete question-answer adjacency pairs in order to manage the conversation. The study also highlighted how a focus on the beginner's L1 enabled them to take greater control in the conversation, despite their very limited L2 speaking ability. In these sections of NNS-dominant communication, the L2 beginner demonstrated greater language creativity. This study has implications for how NS-NNS communication might be facilitated in English-immersion contexts as well as project implications for autonomous learners and teachers.